PERBANDINGAN EVALUASI BENTUK ESSAY DAN MULTIPLE CHOICE WITH REASONING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PENDIDIKAN AGAMA ISLAM KELAS VIII SMP 2 PATAMPANUA - Cania, Murni; Mulianah, Sri; Hamdanah; Amiruddin Mustam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is a skill that students need to have to support the success of the learning process, especially in Islamic Religious Education. Initial observations indicate that this ability is still not optimal, especially in terms of analyzing information, understanding problems, and conveying reasons logically. This study uses a quantitative approach with a quasi-experimental design. The study involved two groups, namely class VIII.2 as the control group using essay-based evaluation and class VIII.4 as the experimental group applying multiple-choice evaluation with reasoning. Research data were collected through pre-test and post-test implementation, then analyzed using descriptive and inferential statistics with the help of the IBM SPSS Statistics 26 program. The results of the study showed an increase in critical thinking skills in both classes. In the control class, the average score increased from 62.88 to 73.40, while in the experimental class it increased from 62.87 to 82.50. In addition, the results of the Independent Sample T-Test produced a significance value of 0.000 which is smaller than 0.05, thus indicating a significant difference between the two forms of evaluation. Thus, multiple choice evaluation with reasoning is proven to be more effective in improving students' critical thinking skills compared to essay-based evaluation..